Integrated Education Programs and Their Role in Developing Creativity Competencies Among Students of the College of Physical Education and Sports Sciences - Entethar Soran (Jurnal Ilmiah Sport Coaching and Education, 2025)
ABSTRACT The current research aims to assess the extent of integration within educational programs offered by colleges of physical education and sports sciences, as perceived by faculty members. It also explores the level of creative competencies exhibited by students in these colleges from the faculty's perspective. Furthermore, the research investigates the impact of integrated educational programs on enhancing students' creative capabilities. A descriptive research methodology was employed, incorporating both survey and correlational approaches. The study population consisted of faculty members from the colleges and departments of physical education and sports sciences at the Universities of Mosul and Al-Hamdaniya, encompassing four institutions (colleges and departments) and 296 faculty members. The primary research sample was randomly divided into three subgroups: an exploratory group, a preparation group, and a final application group, comprising 15, 168, and 112 participants, respectively. Data collection involved the development of two structured questionnaires: one focused on the characteristics of integrated education programs, and the other on students' creative competencies. These instruments were validated and administered to the designated samples. The collected data were analyzed using various statistical techniques, including means, standard deviations, Pearson correlation coefficients, the Spearman-Brown prophecy formula, and linear regression analysis. The findings revealed a statistically significant positive correlation between the implementation of integrated education programs and the development of creative competencies among students. The results suggest that such programs play a critical role in enhancing students’ innovative thinking, athletic performance, and overall engagement by fostering a supportive and enriching educational environment, which positively impacts their performance during lessons.   Keywords: Integrated Education Programs, Creativity Competencies